How does it feel to be a problem? The Diasporic Identity of the Homeless - Asadi, Muhammed (Qualitative Sociology Review, 2013)
In this paper I uncover the identity response of the homeless to structural constraints that are facilitated through objectively produced and mass mediated culture. After an initial period of “liberation,” physical deprivation leads the homeless to seek institutionalized help. The “homeless” category constructed by the shelter industry absolves the system of blame and obfuscates the systemic roots of homelessness. In their picking and dropping of identities, and negotiations of meaning without any referential space to root themselves in, the homeless reveal to us the cultural tragedy of the present that affects us all due to rapid social change inherent in advanced capitalism.